Manganese causes neurotoxic iron accumulation via translational repression of amyloid precursor protein and H‐Ferritin. Issue 6 (19th November 2018) - Venkataramani, Vivek; Doeppner, Thorsten R.; Willkommen, Desiree; Cahill, Catherine M.; Xin, Yongjuan; Ye, Guilin; Liu, Yanyan; Southon, Adam; Aron, Allegra; Au‐Yeung, Ho Yu; Huang, Xudong; Lahiri, Debomoy K.; et al.
Abstract: For more than 150 years, it is known that occupational overexposure of manganese (Mn) causes movement disorders resembling Parkinson's disease (PD) and PD‐like syndromes. However, the mechanisms of Mn toxicity are still poorly understood. Here, we demonstrate that Mn dose‐ and time‐dependently blocks the protein translation of amyloid precursor protein (APP) and heavy‐chain Ferritin (H‐Ferritin), both iron homeostatic proteins with neuroprotective features. APP and H‐Ferritin are post‐transcriptionally regulated by iron responsive proteins, which bind to homologous iron responsive elements (IREs) located in the 5′‐untranslated regions (5′‐UTRs) within their mRNA transcripts. Using reporter assays, we demonstrate that Mn exposure repressed the 5′‐UTR‐activity of APP and H‐Ferritin, presumably via increased iron responsive proteins‐iron responsive elements binding, ultimately blocking their protein translation. Using two specific Fe 2+ ‐specific probes (RhoNox‐1 and IP‐1) and ion chromatography inductively coupled plasma mass spectrometry (IC‐ICP‐MS), we show that loss of the protective axis of APP and H‐Ferritin resulted in unchecked accumulation of redox‐active ferrous iron (Fe 2+ ) fueling neurotoxic oxidative stress. Enforced APP expression partially attenuated Mn‐induced generation of cellular and lipid reactive oxygen species and neurotoxicity. Lastly, we could validate the Mn‐mediated suppression of APP and H‐Ferritin in two rodent in vivo models (C57BL6/N mice and RjHan:SD rats) mimicking acute and chronic Mn exposure. Together, these results suggest that Mn‐induced neurotoxicity is partly attributable to the translational inhibition of APP and H‐Ferritin resulting in impaired iron metabolism and exacerbated neurotoxic oxidative stress. Open Science Badges: This article has received a badge for *Open Materials* because it provided all relevant information to reproduce the study in the manuscript. The complete Open Science Disclosure form for this article can be found at the end of the article. More information about the Open Practices badges can be found athttps://cos.io/our-services/open-science-badges/ . Abstract : For more than 150 years, it is known that occupational overexposure of manganese (Mn) causes movement disorders resembling Parkinson's disease (PD) and PD‐like syndromes. Here, we demonstrate that Mn exposure results in suppression of amyloid precursor protein (APP) and H‐Ferritin in vitro and in vivo . On the molecular level, it could be shown that Mn inhibits the protein translation via repressing the 5'‐UTR activity of both proteins. Mn‐mediated suppression of both iron‐regulating proteins results in an accumulation of redox‐active iron (Fe 2+ ) that fuels neurotoxic cellular oxidative stress and lipidperoxidation. APP overexpression significantly attenuate Mn‐induced oxidative stress and neurotoxicity. The implications that Mn exposure results in a translational suppression of APP and H‐Ferritin links a disturbed iron homeostasis with Mn‐induced oxidative neurotoxicity. Open Science: This manuscript was awarded with the Open Materials Badge. For more information see:https://cos.io/our-services/open-science-badges/